Black Humour and Desensitization: Attitudes of Internet Users Towards the Culture of Excess and Fake News - Cyrek, Barbara (Media - Culture - Social Communication, 2019)
The aim of the author of this article is to characterize phenomena occurring in interactive media: black humour and social desensitization, in the context of digital culture. The author asks the question of whether the awe and absurdities prevailing in the media are the result of desensitization or if they play a compensating function. Providing a definite answer would be a diagnosis of the postmodern human condition. It seems, however, that the media studies do not have tools to allow such an answer.